IEEE Virtual Reality 2004
DOI: 10.1109/vr.2004.1310072
|View full text |Cite
|
Sign up to set email alerts
|

Testbed evaluation of navigation and text display techniques in an information-rich virtual environment

Abstract: The fundamental question for an information-rich virtual environment is how to access and display abstract information. We investigated two existing navigation techniques:Hand-Centered Object Manipulation Extending Ray-casting (HOMER) and Go-Go navigation, and two text layout techniques: within-the-world display (WWD) and heads-up display (HUD). Four search tasks were performed to measure participants' performance in a densely packed environment. HUD enabled significantly better performance than WWD and the Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A few studies investigated the position of text in virtual environments. In a study, Chen et al [6] investigated within-the-world display (WWD) and head-up display (HUD) text layouts while using them with two navigation techniques for search tasks. The results showed that with HUD, participants' performance was higher than with the WWD.…”
Section: Text Presentation and Location In Virtual Environmentsmentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies investigated the position of text in virtual environments. In a study, Chen et al [6] investigated within-the-world display (WWD) and head-up display (HUD) text layouts while using them with two navigation techniques for search tasks. The results showed that with HUD, participants' performance was higher than with the WWD.…”
Section: Text Presentation and Location In Virtual Environmentsmentioning
confidence: 99%
“…Chen et al [6] developed a taxonomy for text layouts in VR by classifying text presentation techniques using the dimensions visual attributes, location, and embedded text quantity. Several researchers provided design recommendations for visual attributes of text, such as font type, font size, text drawing styles, and background color [9,20].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bell et al, 2001), Information Rich Virtual Environments (IRVEs) (e.g. Chen & Bowman, 2004), Information Visualization and Cartography (e.g. Hartmann et al, 2005):…”
mentioning
confidence: 99%